Optimal PID Controller designing for voltage control of Fuel Cell - Omid Khezri; Seyed Jalal Seyed Shenava (Bulletin of Electrical Engineering and Informatics, 2014)
This paper is proposed a PID optimal controller in order to control of one of the most important types of fuel cell, namely proton exchange membrane fuel cell (PEMFC). At first, the introducing and implementation of PEMFC is present and next, during system load variations the proposed controller is designed. The controller should be designed against the load variations for keeping in a fixed value of Fuel cell output voltage. Here, the PID Controller is used which its coefficients are optimized based on Invasive Weed Optimization (IWO). In order to use this algorithm, at first, problem is written as an optimization problem which includes the objective function and constraints, and then to achieve the most desirable controller, IWO algorithm is applied to solve the problem. Simulation results are done for various loads in time domain, and the results show the efficiency of the proposed controller in contrast to the previous controllers.